Difficult‐to‐treat‐depression: what do general practitioners think?. (29th October 2013) - Jones, Kay M; Castle, David J; M Curran, Eleanor; Piterman, Leon
Abstract: Objective: To understand the perspectives of a group of general practitioners regarding management of patients with difficult‐to‐treat depression (DTTD). Design, setting and participants: A qualitative approach using a focus group and semi‐structured telephone interviews conducted in 2011 with 10 GPs from urban and rural Victoria. Five main topics were explored: (1) understanding of DTTD; (2) understanding of other terms used to describe DTTD; (3) experiences of diagnosing DTTD; (4) experiences of managing DTTD; and (5) management options. Results: The participants had generally poor recognition of diagnostic terms, and questioned their relevance. Participants felt that management guidelines were not always helpful. Access to psychiatrists was often difficult, and non‐pharmacological or complementary treatments were considered to have a role in management. Environmental and cultural factors, social isolation and cost of treatment have an impact on patient adherence, and the participants felt that the professional–patient relationship is important in ensuring comprehensive care. Conclusions: Despite extensive experience and knowledge of their patients, there were gaps in GPs' appraisal of the literature and about specific resources available. The GPs had little interest in the nuances of classifications; instead, their focus was on their patient and what to do in practical terms regarding optimal management.